Helicobacter pylori infection associated with type 2 diabetic nephropathy in patients with dyspeptic symptoms. Issue 3 (December 2015) - Zhou, Fei; Zhong, Xiaoqin; Chen, Jingbo; Li, Chunguo; Shang, Ming; Jiang, Cheng; Yang, Hairong; Zhao, Weidong; Liu, Liqiu
Highlights: The association of H. pylori infection and diabetic nephropathy was studied. H. pylori infection is associated with increased proteinuria in diabetics. Patients with diabetic nephropathy are at high risk for infection by H. pylori . High levels of TNF-α and IL-8 are detected in H. pylori  + diabetics. Gastroduodenal lesions do not associated with diabetic nephropathy. Abstract: Aims: The aim of this conventional case–control study was to investigate the prevalence and relationship between Helicobacter pylori infection in type 2 diabetes mellitus (DM) and diabetic nephropathy (DN). Methods: A total of 241 type 2 DM patients and 69 non-diabetic subjects with dyspeptic symptoms were enrolled in the study. Gastroduodenal lesions were observed by gastrointestinal endoscopy and the presence of H. pylori was identified by rapid urease test and serum IgG antibodies to H. pylori . According to the urinary albumin excretion rate (UAE), patients were classified into diabetes mellitus group (DM group, with UAE <30 mg/24 h); diabetic nephropathy group 1 (DN group 1, with UAE 30 mg/24 h to <300 mg/24 h); and diabetic nephropathy group 2 (DN group 2 ≥ 300 mg/24 h). The 69 non-diabetic subjects were used as control group. The serum levels of inflammatory factors such as tumor necrosis factor-α (TNF-α) and interleukin (IL)-8 were determined using ELISA. Results: T he prevalence of H. pylori infection in DN group 1 and DN group 2 was 45/72 (62.5%) and 34/53 (64.15%), respectively, which was significantly higher than in control [28/65 (43.1%)] and DM groups [42.9% (27/63)]. No significant differences of H. pylori prevalence were detected between DN groups as well as DM and control groups. Interestingly, in both DN groups, higher levels of IL-8, TNF-α and urinary albumin excretion rate were found in H. pylori positive subjects. Conclusions: Diabetic nephropathy patients are more susceptible to H. pylori infection. Our data support an association between H . pylori infection and diabetic nephropathy.